Perspectives on Stock Theft Prevention in the Selected Provinces of South Africa: Failures and Successes - Maluleke, Witness; Tshabalala, Ntwanano Patrick; Tolla, Aden Dejene (International Journal of Criminology and Sociology, 2021)
Residents of Limpopo (LIM) and KwaZulu-Natal (KZN) Province are witnessing higher rates of stock theft, with the inhabitants of the selected communities living in fear for the prevention of this scourge. This study explores the extent of this crime in the selected areas of LIM and KZN, considering contributory factors, determining the relationship between the South African Police Service Stock Theft Units (SAPS STUs) and other relevant stakeholders, as well as looking at existing strategies (And their failures and successes) in responding to this crime effectively. A qualitative research approach coupled with Non-probability: Purposive sampling was used in this study. The targeted population consisted of 113 participants. For data collections, Focus Group Discussions (FGDs), Key Informant Interviews (KIIs), and Observation Schedules were adopted. lack of appropriate preventative measures has led to rise of stock theft, it was, therefore, discovered that both the affected livestock farmers and members of the community lost confidence toward the police, Besides, the perspectives on stock theft prevention in LIM and KZN reflect a greater challenge, with inadequate solutions present, since the current preventative measures are ineffective. Thus, understanding stock theft phenomenon is critical to its prevention as the sector of livestock in South Africa is the contributory key to the value of the agricultural economy.